SYNTHESIS, CHARACTERIZATION AND ACTIVITY PATTERN OF CNFsSUPPORTED Cu/Zr02 CATALYSTS FOR C02 HYDROGENATION TO METHANOL - UDDIN, ISRAF (2015)
A series of novel carbon nanofibers supported copper-Zirconia [Cu/ZrO,/CNFs-0 (CZC)] catalysts were synthesized to investigate hydrogenation of C02 to methanol in a three phase reactor at a low{/ pressure of 20 to 50 bar and temperature of 180 to 240 "C. The physicochemical characterizations of synthesized catalysts were studied by X-ray diffraction (XRD), inductively coupled plasma optical emission spectroscopy (lCP-OES). N2 adsorption-<lesorption. N20 chemisorption, high resolution transmission electron microscopy (HRTEM), temperature programmed reduction (TPR), X-ray photoelectron spectroscopy (XPS) and temperature programmed desorption (C02 & NHJ). The effects of temperature, total pressure and feed gas ratio on the methanol synthesis rate were also investigated.